CARBON FOOTPRINT ESTIMATION IN EGYPTIAN AQUACULTURE FARMS - Tarek FOUDA; Abd-Elrahman ELRAYES; Abd-Elhameed ELHANAFY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study discusses the result of a life cycle assessment (LCA) for three Egyptian aquaculture farms categorized as semi-intensive culture. The cradle-to-grave system was used to calculate the overall carbon footprint of fish unit production. The major data came from a study of three feed factories in Egypt, which included a wide range of feed manufacturing and agricultural practises in order to reveal the varied greenhouse gas (GHG) emissions. Pre-farm, farming, and post-farming were the three stages of the life cycle assessment. Feed manufacture, which was primarily tied to the production and processing of raw materials, was the largest source of GHG emissions for all three processes. GHG emissions were also produced during the transport of raw materials to the factory. GHG emissions were also produced during the transportation of raw materials to manufacturers, as well as feed from factories to fish farms, via ship or road. Energy consumption in feed factories varies due to variances in design technology and manufacturing efficiencies. Feed conversion ratios (FCR) have a significant influence on GHG emissions since more feed is required to produce one kilogramme of fish. The kind of packaging material and energy utilised in the factories had an impact on GHG emissions, as each type had a distinct emission factor (EF). Aside from fingerling production, there are direct and indirect N2O emissions, as well as post-farming operations like packaging, ice serving method, and customer transportation. The conclusions of the investigation revealed that According to the results of the study, the emissions linked with the three farms varied greatly. Hanafy farm had the greatest emissions, with 3.265 kg CO2e/kg fish and 50.917 tonnes CO2e/Season, followed by Hashim farm with 2.259 kg CO2e/kg fish and 45.829 tonnes CO2e/Season, and finally Aly farm with 2.223 kg CO2e/kg fish and 38.864 tonnes CO2e/Season.